Identification and Validation of qRT-PCR Reference Genes for Analyzing Arabidopsis Responses to High-Temperature Stress - Siyu Chen; Qi Cai; Peipei Liu; Jingru Liu; Guanzhou Chen; Hanwei Yan; Han Zheng (Current Issues in Molecular Biology)
Quantitative real-time PCR (qRT-PCR) is an essential tool for analyzing and selecting stable reference genes. In order to screen for suitable reference genes under high-temperature stress conditions in Arabidopsis, this study measured the relative expression levels of 17 candidate reference genes using qRT-PCR. Among these, four are traditional reference genes, while the remaining thirteen are candidate reference genes with no previous reports on their use as reference genes. The expression stability of the candidate reference gene expression was analyzed and evaluated using five methods: ΔCt, geNorm, NormFinder, BestKeeper, and RefFinder. The results indicated that the LHCB4.1 and LHCB5 genes displayed the highest stability in expression under high-temperature stress conditions. To verify the stability of the reference genes, we treated Arabidopsis with high-temperature stress, used the selected LHCB4.1 and LHCB5 as references, and analyzed the expression of the heat-responsive gene HSFA2 using qRT-PCR. The results showed that when LHCB4.1 and LHCB5 were used individually or in combination as reference genes, the relative expression of HSFA2 significantly increased and remained consistent under high-temperature treatment. This indicates that both LHCB4.1 and LHCB5 are suitable reference genes for qRT-PCR analysis in Arabidopsis exposed to high-temperature stress. The novel reference genes identified in this study will serve as a reliable reference standard for gene expression studies in Arabidopsis under high-temperature stress, thereby enhancing the accuracy and comparability of experimental data.